Antimicrobial Resistance Patterns among Bacterial Pathogens Isolated from Clinical Specimens in Sheikh Zaid Hospital, Lahore - Saleem, Mehwish; Majeed, Ayesha; Iqbal, Iqra (International Journal of Molecular Microbiology, 2020)
This retrospective study was conducted to determine antimicrobial resistance patterns of bacterial pathogens among patients suffering from Urinary Tract Infections (UTI’s) at the Pathology laboratory, Sheikh Zaid Hospital, Lahore. A total of 50 samples were collected from the different sources which include pus (n=24), followed by blood (n=14), and urine (n=12). Isolation and characterization of bacterial strains was done by conventional cultural, and biochemical methods for microbial enumeration. Antimicrobial susceptibility of bacterial isolates against penicillin, cefotaxime, tetracycline, augmentin, ciprofloxacin, and imipenem was tested by the disk diffusion method. The results revealed a higher prevalence of UTI’s among females (71%) than males (36%). Prevalence of bacterial isolates was Enterococcus faecalis (42%), followed by Staphylococcus aureus (40%), and Streptococcus pneumoniae (18%). Among the six antibiotics tested, bacterial isolates were more resistant to Penicillin; with S.pneumoniae (100%), E.faecalis (98%), and S.aureus (85%). The majority of the bacterial isolates were resistant to penicillin that is mostly prescribed antibiotic and illustrated that more consumption of a specific antibiotic leads to the sustainability of resistance against those antibiotics.